Development and Validation of a Virtual Moving Auditory Localization (vMAL) Test among Healthy Children - Hilmi Che Hassan, Muhammad Nur; Zakaria, Mohd Normani; Wan Mohamad, Wan Najibah (International Journal of Statistics in Medical Research, 2022)
Introduction: The ability to localize sound sources is crucial for humans. Due to specific hearing disorders, the affected individuals may have problems to accurately locate the sound sources, leading to other unwanted consequences. Nevertheless, a simple auditory localization test (that employs moving auditory stimuli) is currently lacking in clinical settings. Essentially, the objectives of the present study were to develop a virtual moving auditory localization (vMAL) test that is suitable for assessing children and assess the validity and the reliability of this test. Materials and Methods: This study consisted of two consecutive phases. In phase 1, the required stimulus and the test set up for the vMAL test were established. Two loudspeakers were employed to produce five virtual positions, and eight different moving conditions were constructed. In phase 2, 24 normal-hearing Malaysian children (aged 7-12 years) underwent the vMAL test. The validity and the reliability of this test were then assessed using several validation measures. Fleiss Kappa and Spearman correlation analyses were used to analyse the obtained data. Results: The vMAL test was found to have good convergent validity (kappa = 0.64) and good divergent validity (kappa = -0.06). Based on the item-total correlation and Spearman coefficient rho results, this test was found to have good internal reliability (rho = 0.36-0.75) and excellent external (test-retest) reliability (rho = 0.99). Conclusions: in this study a new vMAL test was developed and proven to be valid and reliable accordingly for its intended applications. This test can be useful in clinical settings since it is simple to administer, cost-effective, does not take up much room, and can assess auditory localization performance in children. The outcomes of the present study may serve as preliminary normative data as well as guidelines for future auditory localization research.